Investigations of a combustible inertial launch design - Yemets, V.; Prince, Simon A.; Wilkinson, Ray (British Interplanetary Society, 2015)
The paper develops a subject of a combustible inertial (self-feeding) launch vehicle for nano and pico satellites. A part of the paper considers a flight of the rocket using ballistic, aerodynamic and thermal calculations. Another part describes experimental investigations of a laboratory-scale model of the rocket engine. Plans for future work and prospects of the self-feeding technology combined with pulse engine mode for microlaunchers and small satellite micro propulsion concludes the paper.
Keywords: Combustible inertial LV; Self-feeding rocket propulsion